The effects of dietary macronutrients on flight ability, energetics, and fuel metabolism of yellow‐rumped warblers Setophaga coronata. (January 2017) - Guglielmo, Christopher G.; Gerson, Alexander R.; Price, Edwin R.; Hays, Quentin R.
Abstract : The catabolism of protein from organs and muscles during migratory flight is necessary to produce glucose, key metabolic intermediates, and water, but may have negative effects on flight range and refueling at stopovers. We tested the hypothesis, suggested by previous studies, that birds that eat high‐protein insect diets use more protein for fuel in flight than those that eat high‐carbohydrate fruits. First, we fed migratory yellow‐rumped warblers synthetic fruit or mixed insect/fruit diets, and measured metabolic rates and fuel mixture under basal conditions and during exercise in a hop/hover wheel respirometer. Birds eating the fruit diet had greater plasma triglyceride and non‐esterified fatty acid concentrations, and the higher protein mixed diet increased plasma uric acid only during feeding. Diet did not affect metabolic rates or the fuel mixture under resting or exercise conditions. We then fed yellow‐rumped warblers synthetic diets that differed only in the relative proportion of carbohydrate and protein (60:15 versus 15:60 as % dry mass) and tested them in wind tunnel flights lasting up to six hours. Birds fed the high carbohydrate diet became heavier and fatter than when fed the high protein diet. Plasma uric acid concentration was increased and plasma phospholipid concentration was decreased by the high protein diet in the pre‐flight state (after a 3 h fast), but diet only affected plasma phospholipids during flight (lower in high protein birds). Neither diet nor amount of body fat affected the rate of loss of lean mass or fat during flight. Inter‐individual or seasonal differences in diet do not appear to influence the amount of protein catabolized during endurance flight. However, birds fed the high carbohydrate diet had greater voluntary flight duration, independent of body fatness, suggesting that there may be other performance benefits of high carbohydrate diets for migratory birds.